Gallbladder Paraganglioma: Computed Tomography and Magnetic Resonance Imaging Findings - Mustafa Koplay; Mesut Sivri; Hüsnü Alptekin; Hasan Erdoğan; Alaaddin Nayman (Prague Medical Report, 2014)
Paragangliomas are benign tumors that can be association with sympathetic and parasympathetic nerves. More rarely, they can be located in the gallbladder. In this paper, we describe the appearance of an unusual case of paraganglioma in the gallbladder.